Radiographic Evaluation of Root Canal Fillings in a Selected Yemeni Population: A Retrospective Study - Madfa, Ahmed; Al-Hamzi, Mohsen; Al-Sanabani, Fadhel; Saeed, Mohammed; Senan, Elham (University of Concepci?n in Chile, 2016)
Aim: To assess the root canal filling quality performed by general dental practitioners in Yemen through radiographic evaluation. Materials and Methods: Four hundred fifty-five digital panoramic radiographs were selected from the archive of the Dental Health Center in Sana'a, Yemen. The final sample consisted of 221 patients, 685 teeth, and 977 root canals. The criteria for overall radiographic adequacy of root canal fillings were defined as the presence of adequate length, density and taper, and absence of iatrogenic errors (ledges, transportations and perforations). Chi-square test was used to determine statistical significance between different parameters. Results: This study considered only radiographic criteria for evaluation of the root canal fillings. The percentage of root canal fillings with adequate length, density and taper was 30.8%, 29.6% and 20.7%, respectively. Considering the incidence of iatrogenic errors, perforations were present in 12 root canals (1.2%), while the presence of transportations was observed in 20 root canals (2.0%). However, ledges were no detected in any root canals. Conclusion: The root canal filling quality performed by general dental practitioners in Yemen is poor.